Jacob's new dress - Hoffman, Sarah; Hoffman, Ian 1962-; Case, Chris 1976- (Chicago, Illinois Albert Whitman & Company, 2014)
Jacob, who likes to wear dresses at home, convinces his parents to let him wear a dress to school, too.
Keywords: Gender identity -- Fiction; Sex role -- Fiction; Dresses -- Fiction; Clothing and dress -- Fiction